2011
DOI: 10.3892/or.2011.1538
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA-induced TLR3 activation inhibits angiogenesis and triggers apoptosis of human hepatocellular carcinoma cells

Abstract: Abstract. toll-like receptor 3 (tLr3) is a member of the toll-like receptors which recognize pathogen-associated molecular patterns leading to the activation of the innate immune response. recent reports have strongly indicated that they play important roles in cancer cells. since tLr3 has been recently suggested as a possible therapeutic target in certain types of cancers, in the present study, tLr3 expression and its function were explored in hepatocellular carcinoma (HCC) and human umbilical vein endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Poly (I:C) impairs cell proliferation by inducing cell cycle progress inhibition and cell apoptosis via TLR3 in EPCs. For example, Guo et al [ 40 ] found that rat aortic ring outgrowth and endothelial cell tube formation are suppressed after treatment with dsRNA and that dsRNA triggers apoptosis of the MHCC97H, SMMC-7721, and HUVEC cell lines and inhibits cell migration. Our findings are consistent with studies showing that MVD and EPCs correlate negatively with the expression of TLR3 signaling-pathway proteins in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Poly (I:C) impairs cell proliferation by inducing cell cycle progress inhibition and cell apoptosis via TLR3 in EPCs. For example, Guo et al [ 40 ] found that rat aortic ring outgrowth and endothelial cell tube formation are suppressed after treatment with dsRNA and that dsRNA triggers apoptosis of the MHCC97H, SMMC-7721, and HUVEC cell lines and inhibits cell migration. Our findings are consistent with studies showing that MVD and EPCs correlate negatively with the expression of TLR3 signaling-pathway proteins in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In HepG2 (liver carcinoma) cells and hepatocellular carcinoma cells, TLR3 induced apoptosis without an induction of pro-inflammatory cytokines [112,113,114,115]. With regard to TLR3-mediated apoptosis in SS, Manoussakis et al were the first to report a unique type of cell death in which morphologically TLR3 ligand poly I:C induced detachment-induced cell death, or so-called “anoikis” [116].…”
Section: Tlr3-mediated Apoptosis In Sjögren’s Syndromementioning
confidence: 99%
“…[52,53] Actually poly(I:C)-induced TLR3 signaling not only directly induced the apoptosis, but also destroyed tumor microenvironment by suppressing angiogenesis in human hepatocellular carcinoma cell lines MHCC97H and SMMC-7721. [54] Moreover, Shime et al found activation of TLR3 by poly(I:C) converted tumor supporting macrophages to tumoricidal effectors in mice. [55] Excitingly, novel strategies that target TLR3 to fight cancer have been emerging.…”
Section: Resultsmentioning
confidence: 99%